Implementation of the Farmer Card Program Policy in Increasing Community Empowerment Farmer Groups (Case Study at the Gorontalo Regency Agriculture Office) - Habibah U. Abuba; Udin Hamim; Ellys Rachman (Universitas Muhammadiyah Palu, 2024)
The purpose of this research is to find out and analyze the implementation of the Farmer Card Program in increasing the empowerment of the Farmer Group Community in Gorontalo Regency. And Analyze what factors hinder the implementation of the Farmer Card Program to the Farmer Group Community in Gorontalo Regency. This research uses descriptive research with a qualitative approach, the data consists of primary data obtained through open and in-depth interviews with informants and secondary data comes from various sources including journals, theses, books, and previous research. The results of this study indicate that: a) The implementation of the farmer card program at the Gorontalo Regency Agriculture Office has not yet distributed all farmer cards to the Farmer Group Community. b) The community has not utilized the farmer card and still uses manual redemption of fertilizers at official retail kiosks. c) There are still many farming communities that have not been recorded in e-Alokasi. Furthermore, 5 things that become inhibiting factors for the Implementation of the Farmer Card Program, namely: a) Transfer of Services from Bank BNI to Bank BRI. b) Limited Human Resources at the Agricultural Extension Office (BPP) in each District. c) Changes in regulations from the Central Government and regulations from Pupuk Indonesia from the Electronic Group Needs Definitive Plan (e-RDKK) then transferred to Electronic Allocation (e-Allocation). d) Lack of Knowledge and understanding of the community in using the farmer card because it is related to technology. e) There is a new e-Pusluh Program from the government to monitor, evaluate, and organize agricultural extension workers.